2008
DOI: 10.1017/s000711450789430x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D supplementation on bone and vitamin D status among Pakistani immigrants in Denmark: a randomised double-blinded placebo-controlled intervention study

Abstract: Severe vitamin D deficiency is common among Muslim immigrants. The dose necessary to correct the deficiency and its consequence for bone health are not known for immigrants. The aim was to assess the effect of relatively low dosages of supplemental vitamin D on vitamin D and bone status in Pakistani immigrants. This 1-year-long randomised double-blinded placebo-controlled intervention with vitamin D 3 (10 and 20 mg/d) included girls (10·1 -14·7 years), women (18·1 -52·7 years) and men (17·9 -63·5 years) of Pak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 40 publications
7
68
1
1
Order By: Relevance
“…No significant effect of the 1-year long supplementation on any of the lipids was found; suggesting that vitamin D supplementation in small doses does not increase the risk of ischaemic heart disease in this group. The vitamin D supplementation was given to improve bone status; therefore, the power was calculated with regards to an increment in Bone Mineral Density (BMD) (Andersen et al, 2008a). Owing to the low vitamin D status at baseline (Table 1) (Andersen et al, 2008b), the 25-hydroxyvitamin D status only increased to about 45-54 nmol/l (Andersen et al, 2008a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant effect of the 1-year long supplementation on any of the lipids was found; suggesting that vitamin D supplementation in small doses does not increase the risk of ischaemic heart disease in this group. The vitamin D supplementation was given to improve bone status; therefore, the power was calculated with regards to an increment in Bone Mineral Density (BMD) (Andersen et al, 2008a). Owing to the low vitamin D status at baseline (Table 1) (Andersen et al, 2008b), the 25-hydroxyvitamin D status only increased to about 45-54 nmol/l (Andersen et al, 2008a).…”
Section: Discussionmentioning
confidence: 99%
“…The local ethics committee and Danish Medicines Agency approved the study protocol (Andersen et al, 2008a), and the study was carried out in accordance with the Declaration of Helsinki. The written informed consent was obtained from all participants.…”
Section: Methodsmentioning
confidence: 99%
“…Further information about recruitment, tablets, sampling, compliance and biochemical analyses is described elsewhere. 8 Two different measures of body fat were used: body mass index (BMI) was calculated on the basis of anthropometric measures of weight and height (kg/m 2 ) and used as an indirect measure of body fat. Body fat mass and lean mass were measured by wholebody DXA scans from which the body fat percentage (fat mass/ (total weight) × 100%) was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…High bone turnover in vitamin D deficient persons was seen in observational studies (Erkal et al, 2006, Islam et al, 2008, Macdonald et al, 2008). However, the few intervention studies examining the effect of vitamin D supplementation on bone turnover in population such as Caucasian postmenopausal women, young adults and immigrants with low vitamin status have produced mixed results (Grimnes et al, 2012, Macdonald et al, 2013, Andersen et al, 2008). A one year randomized double-blinded placebo-controlled intervention with vitamin D 3 (10 and 20 μg/d) in young women and men of Pakistani origin living in Denmark showed that supplementation increased serum 25(OH)D concentrations and decreased serum parathyroid hormone (PTH) concentrations but there was no significant effect of the intervention on bone turnover markers (Andersen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, the few intervention studies examining the effect of vitamin D supplementation on bone turnover in population such as Caucasian postmenopausal women, young adults and immigrants with low vitamin status have produced mixed results (Grimnes et al, 2012, Macdonald et al, 2013, Andersen et al, 2008). A one year randomized double-blinded placebo-controlled intervention with vitamin D 3 (10 and 20 μg/d) in young women and men of Pakistani origin living in Denmark showed that supplementation increased serum 25(OH)D concentrations and decreased serum parathyroid hormone (PTH) concentrations but there was no significant effect of the intervention on bone turnover markers (Andersen et al, 2008). In another randomized trial, four weeks of daily supplementation with 10 μg vitamin D 3 decreased mean PTH but surprisingly increased tartrate-resistant acid phosphatase (s-TRACP, which is a bone resorption marker) concentration in healthy adults 19–48 years of ethnic Norwegian and Tamil background (Holvik et al, 2012).…”
Section: Introductionmentioning
confidence: 99%